Malaysian Capital Controls - Hood, Ronald D. (World Bank, Washington, DC, 2013)
Malaysian authorities implemented controls on international capital flows late in the Asian crisis, when most of the portfolio outflows had already occurred. The exchange rate had depreciated sharply and was fixed at an undervalued level, making further capital flight unlikely. The turnaround in the stock market, the return of positive GDP growth, the building of reserves, and the relaxation of interest rates all coincided with the imposition of controls. But the same changes took place in other crisis countries that did not follow the same control policies. However, the controls provided insurance against the consequences of possible further disturbances. They created a breathing space for making needed reforms, and the authorities made good use of this time, stabilizing the financial system and pushing ahead with regulatory and supervisory reform for the financial sector and capital markets - a prerequisite for fully liberalizing the capital account. Malaysia incurred a cost: an additional 300 basis point spread paid on floating rate debt for a period after the controls were instituted. But the exit strategy has so far not resulted in lasting flight of portfolio capital. Foreign direct investment remains below precrisis levels, but it is not possible at this stage to attribute this to the effect of controls. On balance, it appears that both the benefits from and the costs of the controls have been modest.